Improvement of PTSD-like behavior by the forgetting effect of hippocampal neurogenesis enhancer memantine in a social defeat stress paradigm - Rie Ishikawa (Molecular Brain, 2019)
Abstract Post-traumatic stress disorder (PTSD) is a psychiatric disorder associated with memories of traumatic experiences. Recent studies have shown that the forgetting of contextual fear memory is promoted via increased adult hippocampal neurogenesis induced by neurogenesis enhancers, such as memantine (MEM) and exercise, raising the possibility that neurogenesis enhancers improve PTSD by facilitating the forgetting of traumatic memory. On the other hand, repeated exposure to social defeat (SD) stress by aggressor mice induces social avoidance behavior to the aggressor and chronic anxiety-like behavior. In this study, we assumed this SD stress paradigm as a PTSD-like model and examined the effects of treatment with neurogenesis enhancer MEM on SD stress-induced PTSD-like behavior. Male C57BL/6 mice received SD stress for 10 consecutive days and were assessed for social avoidance memory to the aggressor (memory of aggressor mice) and anxiety-like behavior using social interaction and elevated zero maze tasks. Consistent with previous studies, SD mice formed social avoidance memory and exhibited increased anxiety-like behavior. Importantly, subsequent MEM treatment (once a week for 4 weeks) significantly reduced social avoidance behavior, suggesting that MEM-treated SD mice showed forgetting of social avoidance memory. Interestingly, MEM-treated SD mice showed comparable anxiety-like behavior with control mice that were not exposed to SD stress. Moreover, MEM-treated SD mice showed no reinstatement of social avoidance memory following single re-exposure to the aggressor. Our findings suggest that neurogenesis enhancer not only enhanced the forgetting of traumatic memory but also improved PTSD (anxiety)-like behavior.